1999
DOI: 10.1101/gr.9.10.895
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Reduction of Chromosome-Specific α-Satellite Array Is Unusually Common in Human Chromosome 21

Abstract: Human centromeres contain large arrays of ␣-satellite DNA that are thought to provide centromere function. The arrays show size and sequence variation, but the extent to which extremely low levels of this DNA can occur on normal centromeres is unclear. Using a set of chromosome-specific ␣-satellite probes for each of the human chromosomes, we performed interphase fluorescence in situ hybridization (FISH) in a population-screening study. Our results demonstrate that extreme reduction of chromosome-specific ␣ sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 60 publications
1
46
1
1
Order By: Relevance
“…In human cells, regular arrays of canonical ␣-satellite repeats are a preferred substrate for kinetochore assembly (28,29). These arrays vary in size from Ͻ200 kb to Ͼ4 Mb without evidence of any impairment of centromeric function (19); however, studies of artificially created minichromosomes and naturally occurring deleted chromosomes suggest that centromeric function depends on a relatively small subdomain of ␣-satellite (30)(31)(32). Considerable evidence also suggests that not all ␣-satellite sequences are functionally equivalent.…”
Section: Mechanism Of Origin Of the Pd-ncmentioning
confidence: 99%
See 2 more Smart Citations
“…In human cells, regular arrays of canonical ␣-satellite repeats are a preferred substrate for kinetochore assembly (28,29). These arrays vary in size from Ͻ200 kb to Ͼ4 Mb without evidence of any impairment of centromeric function (19); however, studies of artificially created minichromosomes and naturally occurring deleted chromosomes suggest that centromeric function depends on a relatively small subdomain of ␣-satellite (30)(31)(32). Considerable evidence also suggests that not all ␣-satellite sequences are functionally equivalent.…”
Section: Mechanism Of Origin Of the Pd-ncmentioning
confidence: 99%
“…To overcome this problem, we used a two-step strategy involving comparing the ␣-satellite DNA on PD-NC4 with that of the Y chromosome (in the two male individuals II:1 and III:1) by using quantitative FISH, followed by PFGE to directly measure the size of the chromosome Y ␣-satellite DNA. For quantitative FISH, we used a pan-␣-satellite probe pTRA7 (18), which under low-stringency conditions has been shown to hybridize to all ␣-satellite sequences (19). The combined results for the two individuals (who both carry the same Y chromosome) showed that the ␣-satellite signal on PD-NC4 was 29% greater than that of the Y chromosome (Fig.…”
Section: No Detectable Pericentric Deletion At the Inactive Centromerementioning
confidence: 99%
See 1 more Smart Citation
“…En effet, il a été montré que les chromatides soeurs de divers chromosomes ne se séparaient pas simultanément mais en fonction de leurs quantités d'hétérochromatine centromérique. L'existence d'une corrélation entre la taille des domaines d'ADN centromérique et les non-disjonctions a été suggérée par plusieurs auteurs [23] et les travaux de K. Maratou et al [24] ont confirmé l'existence d'une relation entre les trisomies 21 de première division méiotique et la taille des blocs d'ADN alphoïdes centromériques des chromosomes 21. Toutes ces altérations des mécanismes de ségrégation méiotique pourraient être mieux tolérées dans le sexe féminin que dans le sexe masculin, puisqu'il semble que les points de contrôle de la méiose femelle soient beaucoup plus « souples » que ceux de la méiose mâle où la présence de chromatides libres bloque la progression méiotique [25].…”
Section: Nouvelles Données Chromosomiquesunclassified
“…More recently, Lo et al (1999) further investigated several chromosomes including 13, 17, and 21 that had reduced centromeric signals and determined that these arrays were approximately 50-100 kb in size. The detection limit of our fluorescent oligoprobes has been estimated at approximately 100 copies (Matera and Ward 1992;C.…”
Section: Wwwgenomeorgmentioning
confidence: 99%